Poverty eradication : a policy framework for country strategies (UNDP New YorkUS, 1995)
Seeks to help UNDP country offices initiate a policy dialogue with their country partners to identify key policy areas and priority actions for the implementation, at the local and national levels, of the World Summit for Social DDevelopment commitments and recommendations, relating to the eradication of poverty.
DC